"Mixed germ cell testicular tumor" in an adult female - Udasimath Shivakumarswamy; R Purushotham; H K Kumar Naik; K R Nagesha (Wolters Kluwer Medknow Publications, 2012)
The androgen insensitivity (testicular feminization) syndrome was described by Morris in phenotypic females with 46XY karyotype, presenting with primary amenorrhea, adequate breast development, and absent or scanty pubic or axillary hair. Gonads consist usually of seminiferous tubules without spermatogenesis. These patients have a 5-10% risk of developing germ cell tumors, usually after the complete development of secondary female sexual characteristics. We hereby report a case considered as a female with married life of 15 years, who was operated for severe abdominal pain. Phenotype characters were that of female. Microscopic examination of the tumor from the abdomen revealed germinoma and yolk sac tumor with adjacent seminiferous tubules. Karyotyping showed 46XY. Final diagnosis of malignant mixed germ cell tumor in androgen insensitivity syndrome was made. Surveillance may be the most appropriate option when these conditions are initially diagnosed in adulthood to prevent development of germ cell tumors.